2017
DOI: 10.3892/etm.2017.5403
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-625 and Fas in cervical vertebral cartilage endplate

Abstract: Abstract. The aim of the present study was to assess miR-625 and Fas expression in normal and degenerative cervical cartilage endplate (CEP) tissues. Following biof-informatics analysis, the Fas gene was predicted to be one of the targets of miR-625. Quantitative PCR (qPCR) and western blotting were used to detect miR-625 and Fas expression in normal and degenerative CEP. A luciferase reporter assay was used to identify whether miR-625 could directly target the 3' untranslated region (3'-UTR) of Fas. Lentivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Ultimately, that defined the Way of the sages. 138 Zhan would surely have assented to these propositions, except perhaps Wang's liberal reading of the value of Buddhist insight into nature and destiny. On the one hand, Wang's confident claim that "Ganquan's 甘泉 [i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, that defined the Way of the sages. 138 Zhan would surely have assented to these propositions, except perhaps Wang's liberal reading of the value of Buddhist insight into nature and destiny. On the one hand, Wang's confident claim that "Ganquan's 甘泉 [i.e.…”
mentioning
confidence: 99%
“…But if he really does, I haven't seen it!" 140 In a parting preface written for a colleague about one month earlier, Zhan had asserted that if a person knows what makes a Ru (scholar) a Ru, he will understand why a Buddhist is different. Practitioners of both traditions experience tranquility and motion.…”
mentioning
confidence: 99%
“…IDD has been shown to be closely associated with apoptosis of nucleus pulposus cells. 49 The pathology of IDD is influenced by decreases in the composition and synthesis of the extracellular matrix because of a reduction in the activity of the intervertebral disc cells due to increased cell apoptosis. 50 The PPI showed that RAB1A, RAB1B, and MCFD2 played important roles in disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was demonstrated that upregulation of miR-34a expression in human degenerated chondrocytes caused Fas-mediated CEP chondrocyte apoptosis (110). Similar to miR-34a, downregulation of miR-625 also caused Fas-mediated cervical CEP chondrocyte apoptosis (111). These findings may indicate that the effects of miRNAs on chondrocyte apoptosis in the CEP may be mediated by Fas.…”
Section: Mirnas and Cep Changesmentioning
confidence: 99%
“…The occurrence of IDD may be associated with CEP degeneration, dysfunction, and calcification (108,109). Some miRNAs (110)(111)(112)(113)(114) have been found to be involved in the changes of the CEP in the progress of IDD (Table V).…”
Section: Mirnas and Cep Changesmentioning
confidence: 99%